THE EFFECT OF ASSETS STRUCTURE AND FIRM SIZE ON FIRM VALUE MEDIATED BY CAPITAL STRUCTURE - Eka Wulan Sari; Elly Siswanto (Journal of Management and Informatics, 2022)
This paper aims to investigate how the effect of Assets Structure and Firm Size on Firm Value Mediated by Capital Structure in Non-Financial Sector Companies Listed on the Indonesia Stock Exchange period 2013-2021. The research method used in this research quantitative An empirical research was conducted with a quantitative approach using panel regression OLS to estimates the dirrect effect and Partial Least Squares Structural Equation Modeling (PLS-SEM) to estimates indirect effect, by using STATA statistical software. sample selection using purposive sampling and found a sample of 180 companies. From the analysis it was found that capital structure and asset structure have no effect on firm value, Firm size has a negative significant on firm value , asset structure has a negative significant on capital structure, firm size has a positive significant effect on capital structure. In addition, capital structure is able to mediate the relationship between asset structure and firm size on firm value. Empirical studies conducted usually only look at the direct effect of the independent variable on the dependent variable, but in this study examines the direct and indirect effects of the independent variables on the dependent variable. In addition, this study does not only use samples from 1 company sector, but using all non-financial sectors companies listed on the Indonesia Stock Exchange